Mapping the past: a database approach to understanding the spread of novel archaeological traits in southern Africa, from 3000 years BP - Lander, Faye Emma (My University, 2020)
2300 years ago marks the beginning of two events in southern Africa’s history. The first is the rapid appearance of non-indigenous livestock and pottery to the western half of the sub-continent. The second, marked by the appearance of cultivation and metal working to the summer-rainfall regions of southern Africa. Archaeologists have long grappled with how to disentangle the archaeology of these spread events –whether the appearance of novel traits marks an exogenous population migration or a transmission and cultural diffusion amongst autochthonous hunter-gatherer communities. Fast-paced genetic research finds migration as the main mechanism for change in the past, yet the research overshadows the role of hunter-gatherers in these processes. A renewed assessment for the archaeology, by an archaeologist, for this time period was thus timely. Five spatially georeferenced and radiocarbon dated southern African databases were compiled and analysed. This is the first time that the archaeology of hunter-gatherers, pastoralists and farmers are presented at a large-scale and at a resolution fine enough to interrogate these events. The open access spatio-temporal archaeological databases offered in the thesis means that this work can be used by other researchers interested in a similar field
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy, 2020